CLINICAL OBSERVATION OF DISCOLORING TREATMENT OF NON-VITAL TEETH BY BLEACHING - O.A. Pysarenko; Yu.I. Silenko; M.V. Khrebor (Український стоматологічний альманах)
A dental cosmetic is actual for everyone. Whitening of teeth can be the method of lab treatmen. Whitening facilities which are used with this goal often contain peroxide, hydrogen, carbamide peroxide, and combinations of peroxides hydrogen with sodium perborate.